Periodization and physical therapy: Bridging the gap between training and rehabilitation. (March 2016) - Hoover, Donald L.; VanWye, William R.; Judge, Lawrence W.
Abstract: Background: Exercise prescription and training progression for competitive athletes has evolved considerably in recent decades, as strength and conditioning coaches increasingly use periodization models to inform the development and implementation of training programs for their athletes. Similarly, exercise prescription and progression is a fundamental skill for sport physical therapists, and is necessary for balancing the physiological stresses of injury with an athlete's capacity for recovery. Objective: This article will provide the sport physical therapist with an overview of periodization models and their application to rehabilitation. Summary: In recent decades models for exercise prescription and progression also have evolved in theory and scope, contributing to improved rehabilitation for countless athletes, when compared to care offered to athletes of previous generations. Nonetheless, despite such advances, such models typically fail to fully bridge the gap between such rehabilitation schemes and the corresponding training models that coaches use to help athletes peak for competition. Greater knowledge of periodization models can help sport physical therapists in their evaluation, clinical reasoning skills, exercise progression, and goal setting for the sustained return of athletes to high level competition.